A photochemical layer-by-layer solution process for preparing organic semiconducting thin films having the right material at the right place. Issue 32 (25th July 2018) - Suzuki, Mitsuharu; Yamaguchi, Yuji; Uchinaga, Kensuke; Takahira, Katsuya; Quinton, Cassandre; Yamamoto, Shinpei; Nagami, Naoto; Furukawa, Mari; Nakayama, Ken-ichi; Yamada, Hiroko
Abstract : A mild and versatile solution process enables the controlled preparation of multicomponent organic small-molecule thin films. Abstract : The synergistic action of properly integrated semiconducting materials can bring about sophisticated electronic processes and functions. However, it is often a great challenge to achieve optimal performance in organic devices because of the limited control over the distribution of different materials in active layers. Here, we employ a unique photoreaction-based layer-by-layer solution process for preparing ternary organic photovoltaic layers. This process is applicable to a variety of compounds from wide-band-gap small molecules to narrow-band-gap π-extended systems, and enables the preparation of multicomponent organic semiconducting thin films having the right compound at the right place. The resulting ternary photovoltaic devices afford high internal quantum efficiencies, leading to an approximately two times higher power-conversion efficiency as compared to the corresponding binary bulk-heterojunction system. This work opens up new possibilities in designing materials and active layers for solution-processed organic electronic devices.